On the Compression Behavior of an Austenitic Fe–18Mn–0.6C–1.5Al Twinning‐Induced Plasticity Steel. Issue 12 (20th June 2013) - Peng, Ching‐Tun; Callaghan, Mark D.; Li, Huijun; Yan, Kun; Liss, Klaus‐Dieter; Ngo, Tuan D.; Mendis, Priyan A.; Choi, Chang‐Ho
Abstract : High manganese austenitic TWIP steels are of great potential in the field of transportation‐related industries owing to their exceptional combination of strength and ductility. A series of compression experiments were conducted on a Fe–18Mn–0.6C–1.5Al alloy at various strain rates (from 1.0 × 10 −2 to 6.4 × 10 3  s −1 ) and total strains (≈15 and ≈20%) with a Gleeble 3500 thermo‐mechanical simulator and a Split Hopkinson Pressure Bar system. Under compressive deformation, results showed this alloy possessed excellent strain‐hardening behavior, attributed to the occurrence of mechanical twinning during deformation. The prevailing deformation mechanism was observed to be twinning, which was substantiated by microstructural analyses, as well as phase identification and evolution of crystallographic texture. Abstract : The compression behavior of Fe–18Mn–0.6C–1.5Al steel is investigated in the strain rate range between 1.0 × 10 −2 and 6.4 × 10 3  s −1 at various total strains. The material is characterized through mechanical property determinations, microstructural analyses, and synchrotron high energy X‐ray diffraction. The prevailing deformation mechanism is observed to be twinning, which is substantiated by microstructural analyses, as well as phase identification and evolution of crystallographic texture.